Reflections on youth partnership in a randomized controlled trial of an intervention to optimize transition from pediatric to adult care in inflammatory bowel disease - Brooke Allemang, PhD, MSW, RSW; Ashleigh Miatello, MA; Pranshu Maini; Joshua Eszczuk; Claudia Tersigni, MSc; Samantha Micsinszki, PhD; Sneha Dave; Natasha Bollegala, MD, MSc, FRCPC; Nancy Fu, MD, MHSc; Kate Lee, PhD, MBA; Samantha J. Anthony, PhD, MSW, RSW; Melanie Barwick, PhD; et al. (Health Care Transitions)
Background: Patient engagement allows for developing health interventions and research studies that align with the needs of people living with chronic diseases. Actively involving people with lived experience as partners in the design and governance of interventional trials is gaining prominence. However, there is a dearth of literature exploring the processes and procedures of patient partnership in various stages of randomized controlled trials (RCTs) with adolescents and young adults (AYAs) with inflammatory bowel disease (IBD), specifically. Methods: This reflective viewpoint outlines how AYA patient partners were involved in a RCT of an intervention to optimize transition from pediatric to adult care in IBD through a Youth Advisory Panel. To achieve this objective, we: i) gathered information from eight members of the study team via virtual discussions, ii) reflected on our experiences collaborating with patient partners in the RCT, and iii) reviewed relevant documents, including meeting minutes. Discussion transcripts, reflections, and documents were reviewed by two academic researchers and one AYA patient partner to identify the varying levels of involvement among AYA patient partners in the trial. The engagement strategies implemented to maximize the translational impact of the multimodal intervention and inform patient-centered care across various stages of the RCT were also examined. Results: The processes, outputs and impacts of AYAs’ contributions in priority setting and planning, intervention design and refinement, study execution, dissemination, and post-trial intervention implementation and dissemination were identified. AYA patient partner motivations for involvement in the RCT and key learnings from this partnership were uncovered. Conclusion: AYA patient partners’ contributions to the RCT were impactful, from study conceptualization to dissemination. Their involvement ensured the intervention's relevance, usability, and youth-friendliness, informed data analysis, and enhanced knowledge translation through co-creation. Future work in this field could involve evaluating the impact of patient engagement on AYA patient partners, research teams, and research outcomes in RCTs.